Insight into antistaphylococcal effect of chlorinated 1-hydroxy-naphthalene-2-carboxanilides - Lucia Vrablova; Tomas Gonec; Petra Majerova; Andrej Kovac; Dominika Kos; Peter Kollar; Jiri Kos; Alois Cizek; Tereza Kauerova; Josef Jampilek (ADMET and DMPK)
Background and purpose: New compounds and innovative therapeutic approaches are trying to prevent antimicrobial resistance, which has become a global health challenge. Experimental approach: This study includes a series of twelve mono-, di- and trichlorinated 1-hydroxynaphthalene-2-carboxanilides designed as multitarget agents. All compounds were evaluated for their antistaphylococcal activity. Furthermore, MTT assay and chemoproteomic analysis of selected compounds were performed. Cytotoxicity in human cells was also tested. Key results: N-(3,5-Dichlorophenyl)-1-hydroxynaphthalene-2-carboxamide (10) demon-strated activity comparable to or higher than clinically used drugs, with minimum inhibitory concentrations (MICs) of 0.37 μM. The compound was equally effective against clinical isolates of methicillin-resistant S. aureus. On the other hand, compound 10 showed 96 % inhibition of S. aureus respiration only at a concentration of 16× MIC. Chemoproteomic analysis revealed that the effect of agent 10 on staphylococci resulted in the downregulation of four proteins. This compound expressed no in vitro cytotoxicity up to a concentration of 30 μM. Conclusion: From the set of tested mono-, di- and trisubstituted derivatives, it is evident that the position of chlorine atoms is decisive for significant antistaphylococcal activity. Inhibition of energy metabolism does not appear to be one of the main mechanisms of action of compound 10; on the contrary, the antibacterial effect may likely be contributed by downregulation of proteins (especially ATP-dependent protease ATPase subunit HslU) involved in processes essential for bacterial survival and growth, such as protein, nucleotide/nucleic acid synthesis and efficient protein repair/degradation.